A practical strategy to access chiral α-aryloxy carboxylic acids through ion-pairing directed asymmetric hydrogenation. Issue 24 (6th November 2020) - Yao, Lin; Ma, Haixia; Nie, Zhuang; Nie, Huifang; Zhang, Dongxu; Wei, Zhao; Shen, Zhanhong; Chen, Weiping; Jiang, Ru; Zhang, Shengyong
Abstract : A series of optically active α-aryloxy functionalized carboxylic acids were obtained via non-covalent interaction assisted highly efficient asymmetric hydrogenation. Abstract : A series of optically active α-aryloxy carboxylic acids were obtained via Chenphos/Rh catalyzed highly efficient asymmetric hydrogenation. The proposed ion-pairing interaction between the ligand and the substrate plays a vital role in achieving high enantioselectivity.